Inconsistency of Court Decisions on Legality of Yogyakarta No.68/KEP/2015 Governor Decree and Compliance - Marsha Merlina Hakim; Mahendra Wardhana (Greenation Research & Yayasan Global Resarch National, 2026)
The dispute over the location determination for Kulon Progo Airport under the Governor of DIY Decree No. 68/KEP/2015 exposes not merely judicial inconsistency among the Administrative Court (PTUN), the Administrative High Court, and the Supreme Court, but a deeper doctrinal ambiguity in Indonesian administrative law. This article argues that the core issue is not simply whether the decree fulfills the criteria of a State Administrative Decision (KTUN), but the absence of a coherent framework to assess administrative acts with both regulatory and individual characteristics. By analyzing the divergent rulings, this study demonstrates that the Supreme Court’s decision constitutes a critical doctrinal shift. It redefines location determination as a justiciable KTUN and introduces a stricter standard of review that integrates formal legality with substantive compliance, particularly alignment with the Regional Spatial Plan (RTRW). The article’s main contribution lies in proposing the concept of “hybrid administrative decisions” to better capture the legal nature of such decrees. This conceptualization not only clarifies the object of administrative disputes but also strengthens judicial control over land acquisition policies. Ultimately, the study highlights the need for clearer legislative guidance to prevent future interpretative disparities and ensure stronger protection of citizens’ land rights.